2020
DOI: 10.29037/digitalpress.22333
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Single Garlic (Allium sativum) Pickle

Abstract: Single garlic is a type of garlic that has a single clove, also known as single clove garlic, monobulb garlic or single bulb garlic. Traditionally, single garlic was used as medicinal based on its properties as antimicrobial, antiprotozoal, antimutagenic, antiplatelet, antihyperlipidemic and antioxidant. The Alliin substance was presumably as an antioxidant, but it was changed easily to unstable allicin caused by Alliinase enzyme activity which is increased when garlic was chopped, crushed or processed. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…The maximum DPPH scavenging activity was achieved at 36 hours of fermentation with an IC50 value of 83.88 µg/mL. This result is supported by [37], which reported that L. plantarum B1765 has been found to increase the antioxidant activity in single garlic pickles by 11.17% on the 9 th day of fermentation. Research by [17] also reported increased antioxidant activity regarding % DPPH inhibition in jicama extract fermented with L. plantarum, which was twice as high as non-fermented jicama extract.…”
Section: Determination Of Antioxidant Activitysupporting
confidence: 65%
“…The maximum DPPH scavenging activity was achieved at 36 hours of fermentation with an IC50 value of 83.88 µg/mL. This result is supported by [37], which reported that L. plantarum B1765 has been found to increase the antioxidant activity in single garlic pickles by 11.17% on the 9 th day of fermentation. Research by [17] also reported increased antioxidant activity regarding % DPPH inhibition in jicama extract fermented with L. plantarum, which was twice as high as non-fermented jicama extract.…”
Section: Determination Of Antioxidant Activitysupporting
confidence: 65%
“…Single garlic contains inulin (Wikandari et al, 2020) and strong antioxidants such as flavonoids that lower blood sugar, prevent cell damage, restore insulin receptor sensitivity, and increase insulin sensitivity (Batiha et al, 2020;Susanti et al, 2020). The flavonoids reduce the production of Reactive Oxidative Species (ROS).…”
Section: The Characteristic Of Single Garlicmentioning
confidence: 99%
“…Dalam satu gram bawang putih segar mengandung 11-35 mg total senyawa organosulfur [2]. Salah satunya yaitu organosulfur alliin (S-allyl-cystein sulfoxide) yang berperan sebagai antioksidan dalam bawang putih [3]. Jenis dan konsentrasi senyawa bioaktif dari bawang putih bergantung pada kultivar, tahap pematangan, praktik produksi tanaman, lokasi, dan metode pengolahan [2].…”
unclassified